Multi-quality characteristics optimisation on WEDM for Ti-6Al-4V using Taguchi-grey relational theory. (2019) - Sharma, Neeraj; Khanna, Rajesh; Sharma, Yogesh Kumar; Gupta, Rahul Dev
In the present research, Ti-6Al-4V alloy was processed on wire-cut electrical discharge machine (WEDM) and the machining responses were analysed. The effect of machining variables was investigated on cutting speed (CS) and surface roughness (SR). Taguchi technique-based L9 orthogonal array was considered for the planning of experiments. Grey relational theory is used for multi-characteristics optimisation. During the research, it was observed that the best optimal setting for the process parameters is A1 B2 C2 . At the suggested optimal setting, the predicted value of CS was 0.2044 mm/min and SR was 2.162 μm. These values are predicted at 95% confidence level. Scanning electron microscopy (SEM) investigates the surface morphology after the WEDM process. The surface integrity reveals the white-layer, sub-surface cracks and micro-cracks on the machined surface. The crack intensity increases with the increase of discharge energy.